Health and Environmental Impact of Hospital Wastes: Systematic Review - Hela Ghali; Asma Ben Cheikh; Sana Bhiri; Lamia Bouzgarrou; Mohamed Ben Rejeb; Imed Gargouri; Houyem Said Latiri (Dubai Medical Journal)
Introduction: Healthcare activities are generally associated with the production of healthcare waste, a large part of which is assimilated to household waste (packaging, kitchen waste, green waste, etc.) and another category of waste which may have a risk to health and the environment given its nature and typology. This category of waste at risk includes waste at risk of infection such as stinging, sharp waste (needles, blade, scalpel, etc.), and waste at chemical risk. Poor management of hospital waste is a problem in most countries and especially in developing countries. We aimed to determine the health and environmental impacts of the poor management of healthcare waste. Methods: We carried out a systematic review of the French and English literature on the scientific research sites Medline/PubMed and Embase. This research was carried out over 3 months (April–June 2020). The search strategy was used by combining keywords and Boolean operators: Health, Health impact assessment, Hospitals, Medical waste, Waste disposal facilities, Environment, Environment/Epidemiology, Hospital waste, impact, workplace, Environment hazards, Healthcare works, Waste management. Results: It has been clear that the current management of healthcare waste is not capable of adequately preserving human health and environmental contamination from infection. The surveys analyzed showed that if incineration is properly treated, it would be an appropriate treatment method to deal with healthcare waste. However, exposure to pollutants produced by the incineration is still a public health problem. If incineration is seen as a practical solution for dealing with healthcare waste, low-temperature incinerators should be banned and replaced by modern incinerators equipped with air pollution control units. These problems are typical for any developing country which does not have the means to purchase incinerators which are more protective for the environment and equipped with the latest technologies. Conclusions: Thus, autoclaving and microwaves are considered better alternatives for treating healthcare waste. However, these methods are generally not adequate for the disposal of pathological, radioactive, laboratory, and chemotherapy wastes. Therefore, the specific management of healthcare waste is a major concern due to the potentially high risks for human health and the environment.